2015
DOI: 10.1093/mnrasl/slv082
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the dynamical case for a massive black hole in IC10 X-1

Abstract: The relative phasing of the X-ray eclipse ephemeris and optical radial velocity (RV) curve for the X-ray binary IC10 X-1 suggests the He[λ4686] emission-line originates in a shadowed sector of the stellar wind that avoids ionization by X-rays from the compact object. The line attains maximum blueshift when the wind is directly toward us at mid X-ray eclipse, as is also seen in Cygnus X-3. If the RV curve is unrelated to stellar motion, evidence for a massive black hole evaporates because the mass function of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…It is thus expected that lowmetallicity stars can produce significantly higher black hole masses than solar-metallicity stars. The heaviest stellar-mass black hole known in our Galaxy is only M ≈ 15 M ⊙ (see [103]; note that previous estimates of the mass of the black hole in IC10 X-1 are unreliable [104]), and the best current thinking is that to produce ∼ 30 M ⊙ black holes the metallicity must be less than ∼ 10 − 50% of solar. In particular, [94] showed that lower metallicities increase the likely masses of black holes and increase greatly the rate of gravitational wave detections.…”
Section: Implications For Black Hole Binary Formationmentioning
confidence: 98%
“…It is thus expected that lowmetallicity stars can produce significantly higher black hole masses than solar-metallicity stars. The heaviest stellar-mass black hole known in our Galaxy is only M ≈ 15 M ⊙ (see [103]; note that previous estimates of the mass of the black hole in IC10 X-1 are unreliable [104]), and the best current thinking is that to produce ∼ 30 M ⊙ black holes the metallicity must be less than ∼ 10 − 50% of solar. In particular, [94] showed that lower metallicities increase the likely masses of black holes and increase greatly the rate of gravitational wave detections.…”
Section: Implications For Black Hole Binary Formationmentioning
confidence: 98%
“…The first unambiguous eclipsing behavior in a candidate BH X-ray binary outside the Milky Way was found in IC 10 X-1, located in a Local Group dwarf galaxy, with a Wolf-Rayet donor star, a binary period of 1.45 days, and an X-ray luminosity » L 10 X 38 erg s −1 (Prestwich et al 2007;Laycock et al 2015a;Steiner et al 2016). For IC 10 X-1, it is still disputed whether the accreting compact object is a BH or a neutron star (Laycock et al 2015b). Outside the Local Group, NGC 300 X-1 ( »Ĺ 5 10 X 38 erg s −1 ; binary period »33 hr) shows X-ray dips, consistent with occultation from geometrically thick structures in the outer disk, or absorption in the wind of the donor star, but not with true eclipses (Binder et al 2015).…”
Section: Table 11mentioning
confidence: 99%
“…Owing to the unique challenges of observing the winddominated Wolf-Rayet companions, the masses of the compact objects in these systems are rather uncertain and, indeed, the presence of a neutron star cannot be ruled out (Binder et al 2015;Laycock et al 2015). Finally, we should also mention ultraluminous X-ray sources (ULXs), systems with X-ray luminosities that are greater than the Eddington limit for a 10 M BH.…”
Section: Introductionmentioning
confidence: 99%